Al-Kalimāt Al-Indūnīsiyyah Dżāt Aslin ‘Arabiy Fī Mu‘Jam KBBI Min Harf “N” Ilā Harf “R” Wa Al-Istifādah Minhā Fī Ta’līm Mahārah Al-Qirāah - Aulia Imani Riyahanna; Arif Taufikurrohman (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2021)
إن الإسلام جاء إلى إندونيسيا عن طريق تجار العرب وهم الدعاة الإسلامية في القرن السابع الميلادي. ومجيء الإسلام يؤدي إلى وجود التأثير لدى الإندونيسيين خاصة من الناحية اللغوية بحيث إنهم أخذوا بعض الكلمات العربية التي لم يعرفوها سابقا، فقامت الباحثة دراسة هذا الموضوع بهدف معرفة الكلمات الإندونيسية ذات أصل عربي في معجم اللغة العربية الكبير (KBBI) من حرف N إلى حرف R. استخدمت الباحثة منهج الوصفي التحليلي. وقد أثبتت هذه الدراسة أن الكلمات ذات أصل عربي من حرف N إلى حرف R في معجم اللغة العربية الكبير (KBBI) بلغ عددها إلى 100 كلمة، وأثبتت أيضا على أنها تنقسم إلى أربعة أقسام؛ هي كلمات عربية بقيت معانيها في اللغة الإندونيسية 59 كلمة، وكلمات عربية ضاقت معانيها في اللغة الإندونيسية 22 كلمة، وكلمات عربية اتسعت معانيها في اللغة الإندونيسية 7 كلمات، وكلمات عربية انتقلت معانيها في اللغة الإندونيسية 12 كلمة. وتمكن الاستفادة منها في تعليم اللغة العربية خاصة في تعليم مهارة القراءة للإندونيسيين من خلال وضعها في صياغة الحوار والنص مع التدريبات. Islam came to Indonesia through Arab traders, who were preachers of Islam in the 7th century AD. The arrival of Islam had a considerable influence in Indonesia, especially in terms of linguistics, because Indonesian people took some Arabic vocabulary that they did not know before. Therefore, in this study the researcher aimed collect vocabulary in Indonesian originating from Arabic contained in The Large Dictionary of Bahasa (KBBI) from the letter N to the letter R. The method used in this research is an analytical descriptive approach. This research has proven that the existence of Arabic vocabulary originating from the letter N to the letter R in The Large Indonesian Dictionary (KBBI) ranges from one hundred vocabularies which can be grouped into four parts, namely Arabic vocabulary whose meaning does not change in language Indonesia, Arabic vocabulary that experiences narrowing of meaning in Indonesian, Arabic vocabulary that has expanded expands its meaning in Indonesian and Arabic vocabulary that changes into other meanings in Indonesian. The researcher assumed that this vocabulary can be used to teach Arabic, especially in teaching Indonesian reading skills, by putting it in dialogue and reading spiked with practice.